2018
DOI: 10.1111/jcpe.12909
|View full text |Cite
|
Sign up to set email alerts
|

Chronic periodontitis is associated with erectile dysfunction. A case–control study in european population

Abstract: Patients with erectile dysfunction showed worse periodontal condition. Chronic periodontitis seems to play a key role as a risk factor in the pathogenesis of erectile dysfunction independently of other morbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 37 publications
3
38
0
3
Order By: Relevance
“…It was found that patients with CP have the risk to develop ED 2.17 times higher than individuals with healthy periodontium. This correlation was independent of other morbidities (Martín et al, 2018). This is also in accordance with the observations of Matsumoto et al (2014) who evaluated the link between ED and CP by a cross-sectional study on 88 Japanese men, and they observed a positive association between CP and ED (Matsumoto et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…It was found that patients with CP have the risk to develop ED 2.17 times higher than individuals with healthy periodontium. This correlation was independent of other morbidities (Martín et al, 2018). This is also in accordance with the observations of Matsumoto et al (2014) who evaluated the link between ED and CP by a cross-sectional study on 88 Japanese men, and they observed a positive association between CP and ED (Matsumoto et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…Also, no X-rays were taken in this study. This is in accordance with these five studies (Eltas et al, 2013;Martín et al, 2018;Oğuz et al, 2013;Sharma et al, 2011;Uppal et al, 2014). In our study, the definition of periodontitis was based on the classification system of periodontal conditions and diseases (Armitage, 1999).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Su principal controlador es el sistema nervioso autónomo, siendo esto un fenómeno eminentemente neurovascular con un mediador universal que es el óxido nítrico. 8,9 Durante la flaccidez, el músculo liso cavernoso (por efecto del sistema adrenérgico sobre receptores alfa1 postsinápticos y alfa2 pre-y postsinápticos) está contraído, lo que hace que el flujo de sangre sea bajo. Cuando se produce el estímulo erótico y la excitación sexual, por vías parasimpáticas y oxitocinérgicas, se envía información a las neuronas no adrenérgicas/no colinérgicas y al endotelio de las arterias del pene, se libera óxido nítrico a partir del aminoácido L-arginina-vía citrulina-por efecto de la enzima óxido nítrico sintetasa, provocando que los vasos del pene se dilaten por acción del guanilato ciclasa, lo que resulta en un nivel aumentado de GMPc, con el ingreso de una mayor cantidad de flujo sanguíneo.…”
Section: Fisiología De La Erecciónunclassified